Former Foster Youth in Postsecondary Education Reaching Higher - Gross, Jacob P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
(3z(BCollege access, affordability, and completion are critical issues facing American higher education today$1 (Bespecially for students who have been in the foster care system. Based on sound data and smart policy analysis, this book will help high school counselors, social workers, and student affairs professionals better support current and former foster youths. It also identifies promising ways policymakers and college leaders can leverage their influence to equalize educational opportunity.(3y $1 (BNicholas Hillman, Associate Professor, Educational Leadership and Policy Analysis, University of Wisconsin-Madison, USA (3z(BBy examining the lives and postsecondary experiences of foster youth, the author sheds light on a marginalized population. As a scholar-practitioner myself, this book is a much needed primer for those who work with college-going foster youth. His work highlights the nuanced and complicated experiences of foster youth when navigating higher education: it unpacks the various challenges they face, the supportive systems that exist, and the necessary work that still needs to be done. As someone who emancipated from the foster care system, I appreciate this work; it is a call to action to (re)shape the discourse of foster youth that is anti-deficit and data driven. This textbook is useful for students and practitioners in higher education, student affairs, and social work.(3y $1 (BKenyon Lee Whitman, Program Director, Guardian Scholars Program, University of California, Riverside, USA.s
1. Introduction -- 2. Benefits of and Barriers to Higher Education -- 3. An Overview: Foster Care and Policies Designed to Support Youth in Care -- 4. Transitions out of Care -- 5. College Readiness and Enrollment Among Baccalaureate Degree Seekers -- 6. How Former Foster Youth Finance Higher Education -- 7. Campus Based Support Programs -- 8. Conclusion -- .
Keywords: Higher education; Educational policy; Education and state; Social policy; Juvenile delinquents; Higher Education; Educational Policy and Politics; Children, Youth and Family Policy; Youth Offending and Juvenile Justice